Investigation of fecal egg counts versus worm burden and helminth fauna in cattle treated or not with macrocyclic lactones in a tropical region - Teixeira, Weslen Fabricio Pires; Gomes, Lucas Vinicius Costa [UNESP]; Felippelli, Gustavo [UNESP]; Buzzulini, Carolina [UNESP]; Zapa, Dina Maraia Beltran; Cavalcante, Alliny Souza de Assis; Borges, Dyego Gonçaslves Lino; Ferreira, Lorena Lopes; Santos, Thais Rabelo dos; Soares, Vando Edesio; Arnhold, Emmanuel; Costa, Alvimar José da [UNESP]; et al. (My University, 2021)
Gastrointestinal nematodes negatively impact the health and productivity of livestock. Macrocyclic lactones (MLs) are the most common class of chemicals used in helminth control programs, however, their intense use is accelerating the development of parasite resistance. For cattle, little is known regarding the relationship between fecal egg counts (FECs) and the helminth population inside the animal's gastrointestinal tract and so this study evaluated the correlation between FEC and worm burden in cattle treated or not with MLs (ivermectin 200 μg/kg, ivermectin 630 μg/kg, abamectin 200 μg/kg, doramectin 700 μg/kg and moxidectin 200 μg/kg). Animals were necropsied to determine if there were any modifications to the proportions of worm species due to chemical treatment. FECs of ML-treated and untreated animals showed significant (p ≤ 0.05 and R2 ≥0.70) positive linear correlations and substantial or perfect strength-of-agreement (LCCC ≥ 0.61) with total worms present, all of which were Haemonchus placei and Cooperia punctata. However, this correlation and strength-of-agreement did not occur when the efficacy of MLs was ≥80 % against these helminths. Among the active MLs tested, moxidectin had the weakest relationship between FEC and worm burden, except for H. placei. Analysis of the helminthological fauna found an increase of H. placei (35.6 % = 95 % CI 35.4–35.6) and a consequent decrease of C. punctata (52.5 % = 95 % CI 52.3–52.6) in untreated animals, when compared to studies carried out over 20–40 years ago, but this proportion was reversed for ML-treated animals (C. punctata 64.5 % = 95 % CI 64.4–64.8; H. placei 30.8 % = 95 % CI 30.6–30.8). It is possible that MLs mitigate this effect in the field and that C. punctata remained prevalent in cattle in different regions of Brazil.
Keywords: Avermectins; Eggs per gram (EPG); Gastrointestinal nematodes